Two women and a typewriter - Unknown:::Creator::::::::::::
Photograph shows a reception area with two women standing on either side of a long counter. One of the women is posing as if typing on an old typewriter which is sitting on the reception desk in the YWCA building on Second Street. They are probably there for the 1973 YWCA annual meeting.